The saga of Billy the Kid - Burns, Walter Noble (Historians of the frontier and American West., 1999)
First published in 1926, this entertaining and dramatic biography forever installed outlaw Billy the Kid in the pantheon of mythic heroes from the Old West and is still considered the single most influential portrait of Billy in this century. Saga focuses on the Kid's life and experiences in the bloody war between the Murphy-Dolan and Tunstall-McSween gangs in and around Lincoln, New Mexico, between 1878 and 1881. Burns paints the Kid as a boyish Robin Hood or romantic knight galvanized into a life of crime and killing by the war's violence and bloodshed. Billy represented the romantic and anarchic Old West that the march of civilization was rapidly displacing. His destroyer was Pat Garrett, the courageous sheriff of Lincoln County. Garrett's shooting of Billy in 1881 hastened the closing of the American frontier. Richard W. Etulain's introduction discusses the singular place of Saga in the historical literature on Billy the Kid and the Lincoln County War."--Jacket